Application of nanotechnology in Eichhornia crassipes extracts - Darawan Limthin; Darinee Phromyothin (My University, 2017)
Natural extracts have widespread application because some can be used as antioxidants in pharmacological cosmetics.In this study, the ethanol extract of the dried leaves of the Eichhornia crassipes was prepared.Nano-emulsion of crude extract was developed by multiple emulsion homogenization techniques.Span 80 and tween 80 were used as emulsifiers in which oil phase and surfactant were virgin coconut oils and nonyl phenol ethoxylate with ratios of water, emulsifier and oil of 80:10:10, 70:20:10 and 70:10:20 and different ratio of coemulsifier between span 80 and tween 80 at 0:2, 0.5:1.5, 1:1, 1.5:0.5 and 2:0.Emulsion extract was homogenized for 10-60 minutes at 2000-4000 rpm.Particles size and electrokinetic potential of emulsion extracts were determined by dynamic light scattering method.The droplet size was decreased by increasing surfactant concentration and time of homogenization.The smallest droplet size of the nano-emulsion consisting of 80:10:10 of water, emulsifier and oil in emulsifier of tween 80: span 80 at the ratio of 7.5:2.5,homogenized for 60 minutes at 2000-4000 rpm.was in the range of 100 to 400 nm.The nano-encapsulation of E. crassipes extract would be potential for the delivery of bioactive compounds.
Keywords: Eichhornia crassipes; Botanical Research and Applications